2021
DOI: 10.1007/s11356-021-16876-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between environmental factors and COVID-19 indices: a global level ecological study

Abstract: This global level ecological study aimed to investigate the correlation between environmental factors and the COVID-19 indices. This survey is an ecological study, so all studied variables are aggregate variables. To collect the variables in the study, a data set was provided, which includes the information of each country based on the cumulative deaths, case fatality rate, recovery rate, and the number of performed COVID-19 tests. Scatter plots of environmental factors for the studied countries were drawn bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Ecological studies have a history of use in public health issues and diseases [ 39 , 40 ]. In this study, limitations related to the method used must be considered and the results must be carefully interpreted as there may be an ecological fallacy.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological studies have a history of use in public health issues and diseases [ 39 , 40 ]. In this study, limitations related to the method used must be considered and the results must be carefully interpreted as there may be an ecological fallacy.…”
Section: Discussionmentioning
confidence: 99%
“…Because the data were collected in the first months of the pandemic, seasonal behaviour of COVID-19 could not be observed [21][22][23][24] and is not represented in the data. To avoid overfitting due to coincidental correlations between time features and the resulting outcome, all time features were removed.…”
Section: B Input Datamentioning
confidence: 99%
“…Possible extensions of this work could be done by repeating the experiments with more data collected over a longer time period or different locations. This might result in a more representative evaluation of the actual importance of time features as SARS-CoV-2 seems to be correlated to seasonal behaviour, but also regarding environmental influences and accessibility of health institutions [21][22][23][24]. Additionally aspects like SARS-CoV-2 mutations, times of vaccination and date of last vaccination could be included and improve the reliability of the model by now.…”
Section: B Future Workmentioning
confidence: 99%
“…The chaos caused by COVID-19 has affected personal and group life in different societies as well as the national and global performances. The economic, social, educational, environmental, and other functional indices changed considerably [2,3]. COVID-19 pandemic incurred massive damages to human societies, such that from the beginning of its outbreak up to 20 January 2022, 336,790,193 confirmed cases of COVID-19, with 5,560,718 deaths have been reported to WHO.…”
Section: Introductionmentioning
confidence: 99%
“…In studies performed on controlling COVID-19, so far healthcare and medical geography, as well as healthcare and medical policies have remained understudied [15]. Considering the rapid and extensive spread of this disease through the air and the inevitable interactions among different societies especially in neighboring countries, as well as genetic, cultural, social and other similarities of these counties, extraterritorial and international communications, as well as inability of some countries in providing the resources required for tackling this disease, global approaches are essential for controlling COVID-19 [3,16,17]. The past experiences of different counties indicated that local decisions on confronting this disease can influence the global community.…”
Section: Introductionmentioning
confidence: 99%